Exploring Request Strategies by Indonesian EFL Learners - Pardede, Ayu; Dirgantari, Alfi Suci; AS, Hilga Clararissa; Susantiningdyah, Healty (Journal of Applied Linguistics, 2025)
Effective communication in an English as a Foreign Language (EFL) setting requires pragmatic competence as it enables EFL learners to use language, particularly to employ request strategies appropriately. However, based on the results of previous studies, EFL learners often face difficulties in selecting request strategies that fit the communicative contexts. Therefore, this study aims to explore the request strategies employed by Indonesian EFL learners and examine the influence of social status and distance on their strategy use. Seventeen upper-intermediate university students enrolled in an English course participated in this study. The data were collected through an open-ended written Discourse Completion Task (DCT) consisting of six scenarios that described various levels of social status and distance between interlocutors. To collect the data, the DCT was distributed through Google Form and participants were asked to freely write their responses for each scenario. The responses provided by participants were analyzed based on the classification of request strategies by Trosborg (1995) through qualitative thematic analysis. The findings reveal that Indonesian EFL learners had a strong preference for conventionally indirect request strategy, particularly by questioning the hearer’s ability/willingness. Moreover, they tended to overgeneralize politeness forms, in which they consistently used conventionally indirect strategy across various social contexts. This finding suggests their inability to adjust strategies in diverse social situations. Additionally, inappropriate use of informal and confrontational language was also found, indicating a need for the development of cross-cultural awareness. The findings of this study imply that Indonesian EFL learners need to enhance their pragmatic competence to navigate diverse social situations effectively in English. Keywords : Pragmatic competence, request strategy, indirectness